Performance analysis of the CDRI diesel engine`s performance and emission parameters blended with leftover cooking oil, additional nanoparticles, and hydrogen enrichment - Dond, Dipak; Barshikar, Raghavendra Rajendra; Ghongade, Harshvardhan; Bhadre, Anjali; Dond, Shantaram (Zielona Góra: Uniwersytet Zielonogórski)
The low cost and wide availability of used cooking oil make it a desirable feedstock for the generation of biodiesel. In this study, Three distinct hydrogen enrichment values (4 lit/min, 6 lit/min, and 8 lit/min) and nanoparticle concentrations of 50, 100, and 150 PPM) are combined with used cooking oil blends (10%, 15%, and 20%) to evaluate the CRDI single-cylinder diesel engine`s efficiency and emission properties.
Keywords: CRDI single cylinder diesel engine; waste cooking oil; hydrogen; TiO2 nanoparticles; performance characteristics